Proses Perubahan Unsur Serapan Bahasa Asing-Indonesia dalam Podcast Close the Door Berjudul 500 Juta Bawa Pulang Sana Bersama Deddy Corbuzier - Sunarto, Muhammad Fikri; Amalia, Nur (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
This study aims to describe every utterence that contains absorption elements and find out the process of change, namely the process of adaptation, adoption, translation, and creation in a podcast entitled 500 Juta Bawa Pulang Sana with Deddy Corbuzier. The method used in this research is descriptive qualitative. The data collection technique used is purposive sampling. Data analysis technique is by listening to video podcasts repeatedly, noting absorption elements and classifying them into analysis tables. The validity of the data was tested using theoretical triangulation and investigation. This Close the Door podcast with Deddy Corbuzier has it’s own uniqueness compared to other podcasts, such as various sources, interesting and current topics of discussion, and entertaining the audience. The results of this study showed that there were 17 absorption elements from foreign languages, including 12 words from English, 1 word from Dutch, 3 words from Arabic, and 1 word from Portuguese. In the change processes, namely 12 words through the adaptation process, 5 words through the adoption process, and there is no translation process or creation process in it.The implication of this research is to be able to know and to understand the origion of words used in daily conversation, especially on Close The Door podcast with Deddy Corbuzier and how foreign languages can enter indonesian into absorption elements along with the process of change.